Ground reaction forces related to athletic performance between international and national weightlifters - Funato, K.; Isaka, T.; Okada, J.; Sekiguchi, O. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Ground Reaction Force (GRF) was measured during the snatch technique of Olympic style weightlifting in order to see how GRF relate to the athletic performance among weightlifters of different athletic levels. Four force platforms (Kistler, type 928 1B) were mounted in the weightlifting platform which enable to detect the three axis of GRFs i.s.,Fx (right and left direction, Fy (front and back) and Fz (vertical direction), in the area of 120 x 80cm. Subjects were six Japanese lifters (including one national lifter in 67,5 kg category: TKD) and two international elite lifters who won the gold medals in 67.5kg (KUN) and +110kg (KUR) categories at the Seoul Olympic Games. Two vertical GRF peaks separated by an "unwieghting" as the double knee bends (DKB) pull in the coaching of weightlifting. In international elite weightlifters, rate of force production in the first and second peaks in Fz were greater than Japanese weightlifters. They also showed a shorter period between first and second peak in Fz (65 - 95ms) compared to that of Japanese elite weightlifter (245ms). Fz and Fy pola curve indicated that the frontal and backward acceleration in Fy was respectively about two and three fold greater in international elite weightlifters than Japanese lifters.